Clinical and diagnostic value of the functional and conformational properties of serum albumin in patients with ovarian cancer (а pilot study) - T. V. Davydova; I. I. Matveeva; A. N. Gritsai; N. R. Pogosyan; L. T. Mamedova; V. V. Kuznetsov (Опухоли женской репродуктивной системы)
The functional properties of serum albumin were examined in patients with ovarian cancer and benign ovarian tumors. The findings make it possible to recommend that the albumin conformation index should be determined for the early diagnosis of ovarian cancer and for evaluation of its treatment.